Thematic Clusters in Education - Anatoliy V. Kupavtsev (Высшее образование в России)
The urgent tasks of the national economy modernization and the need in human resources able and ready for creative work and innovations led to the development of a new educational technology in higher school. Training assignments and exercises are being replaced by selfdirected thinking efforts aimed at understanding of scientific generalizations and professional skills mastering. A modular approach to course design together with competence approach laid down the foundations for a new educational technology of professional education. The paper asserts that modular learning creates a new informal style of communication between students and teachers, which is based on teamwork in specialized educational, engineering centres and labs. Cluster technology combines theory and work experience, reveals features and specifics of subjects. Courses should be practice-oriented, and cluster tasks should be multivariant. Special attention should be paid to control questions. On the whole, cluster learning provides favourable conditions for the development of students’ creative abilities and creative thinking.